Рабочий класс в Украине: хроника потерь - Симончук, Е. (Социология: теория, методы, маркетинг, 2005)
The article deals with various approaches to the definition of “working class”. According to the data of sociological monitoring and social statistics the dynamics of working class number in Ukraine during the last two decades has been analyzed. The directions of occupational mobility for the same time interval are also examined.